The transfer and commercialization program of the Philippine Council for Industry and Energy Research and Development (PCIERD-DOST) from 2001 to 2009 a case study - Tabangcura, Ma. Elena Talingdan (University of the Philippines Diliman, Quezon City Technology Management Center, 2010)
Technology has become not only an important dimension of national development and growth but also as an essential factor for survival in this competitive world. Expectedly, the development, transfer and commercialization of new technologies have become the focus and are considered as forces to reckon with by countries, both developed and developing, in their national development goals. In the past years, particularly form 2001-2009 under the Arroyo Administration, there had been a strong support from the national government for S&T development. This comes with the realization that a technology-backed national economic agenda would certainly lead to progress, thereby, S&T will be made the foundation of future economic development of the country. In response to this, the Department of Science and Technology (DOST) developed its National S&T Plan 2002-2020 or NSTP 2020 (Annex A) which gives the direction of S&T development in the Philippines for the next 10 years. The Plan is supportive of the visions and goals stated in the Medium-Term Philippine Development Plan (MTPDP) which are : macroeconomic stability with equitable growth based on the free enterprise, agriculture and fisheries modernization with social equity, comprehensive human development, and good governance.
This paper focused on the short-term component of the NSTP 2020 which outlines the specific programs that will be given emphasis, namely, R&D, technology transfer, human resource development, S&T promotion, information dissemination and advocacy, and linkaging and networking. It is said that the success of the NSTP in the short and medium term depends upon the implementation of these programs. This paper further looked into the technology transfer and commercialization program of the DOST's Philippine Council for Industry and Energy Research and Development (PCIERD-DOST). The PCIERD is one of the sectoral planning councils of the DOST which takes charge of a diverse set of sectors for development, namely : 1) Food and Feed, 2) Process, 3) Mining and Minerals, 4) Metals and Engineering, 5) Energy, 6) Transportation, 7) Construction, 8) Environment, and 9) Disaster Management. These are critical sectors in the country's economic development. The PCIERD has indeed been conducting technology transfer and commercialization activities but it was only in 2003 that it formally took on the function of transferring technologies and instituting the mechanisms for its commercialization efforts. The PCIERD now conducts Technology Assessments, Technology Demonstrations, Technology Diffusion, and alongside, it has been facilitating the preparation of patent applications for PCIERD-generated technologies. It has also established a mechanism by which the private sector would participate in its S&T activities, as well as taking the academe as its partners and cooperators in R&D. However, there has been a dearth of technology transfers or those that led to commercialization even with the assurance that the technologies being offered by PCIERD underwent exhaustive evaluation with the use of the Technology Assessment Protocol which conducts three-inter-related steps, namely : 1) Technology Pre-Screening/Identification, 2) Technology Scanning, and 3) Technology Validation. This paper looked into this impasse and recommends some plausible actions that PCIERD may consider to strengthen its technology transfer and commercialization mechanisms.
In partial fulfillment of the requirements in TM 299.2
Keywords: Philippine Council for Industry and Energy Research and Development (PCIERD-DOST); Commercialization program